2005
DOI: 10.1074/jbc.m410344200
|View full text |Cite
|
Sign up to set email alerts
|

Full Activation of PKB/Akt in Response to Insulin or Ionizing Radiation Is Mediated through ATM

Abstract: The gene mutated in ataxia telangiectasia, ATM, has been implicated in several cell functions such as cell cycle control and response to DNA damage and insulin. PKB/Akt has also been implicated in the cellular response to insulin, gamma-radiation, and cell cycle control. Interestingly, lack of PKB/Akt function in vivo is able to mimic some phenotypic abnormalities associated with ataxia telangiectasia (AT). Here we show that ATM is a major determinant of full PKB/Akt activation in response to insulin or gamma-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
252
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(278 citation statements)
references
References 38 publications
(37 reference statements)
21
252
2
3
Order By: Relevance
“…We did not detect significant differences in DNA-PK activity in the presence of Mg 2ϩ or Mn 2ϩ (data not shown). Recent observations from ATM Ϫ/Ϫ MEFs or ATM Ϫ/Ϫ , ATR Ϫ/Ϫ double MEFs (31) contrast with the conclusion of Viniegra et al (45), who argued that ATM promotes PKB phosphorylation on Ser-473. It should be noted that ATM Ϫ/Ϫ MEFs in their study were produced from a p53 Ϫ/Ϫ background.…”
Section: Discussioncontrasting
confidence: 46%
“…We did not detect significant differences in DNA-PK activity in the presence of Mg 2ϩ or Mn 2ϩ (data not shown). Recent observations from ATM Ϫ/Ϫ MEFs or ATM Ϫ/Ϫ , ATR Ϫ/Ϫ double MEFs (31) contrast with the conclusion of Viniegra et al (45), who argued that ATM promotes PKB phosphorylation on Ser-473. It should be noted that ATM Ϫ/Ϫ MEFs in their study were produced from a p53 Ϫ/Ϫ background.…”
Section: Discussioncontrasting
confidence: 46%
“…Secondly, Akt has been shown to be a direct phosphorylation target of ATM, an upstream driver of the DDR (Viniegra et al , 2005). To test the relation between ATM, Akt and mTORC1, we induced a DDR in human fibroblasts by X‐ray irradiation and treated them with an ATM inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Boehrs et al (32) suggest that cytoplasmic ATM promotes neuron survival in an insulin-dependent manner. Viniegra et al suggested that ATM is required for full activation of AKT, the key kinase of the insulin pathway (29). Finally, Kim et al demonstrated that AKT and ERK1/2 are constitutively down-regulated in ATM Ϫ/Ϫ neurospheres (35).…”
Section: Discussionmentioning
confidence: 99%